Synergistic treatment strategy: combining CAR-NK cell therapy and radiotherapy to combat solid tumors - He, Jie; Yan, Yushan; Zhang, Jun; Wei, Zhiming; Li, Huashun; Xing, Ligang (Frontiers in Immunology, 2023)
Immunotherapy, notably chimeric antigen receptor (CAR) modified natural killer (NK) cell therapy, has shown exciting promise in the treatment of hematologic malignancies due to its unique advantages including fewer side effects, diverse activation mechanisms, and wide availability. However, CAR-NK cell therapies have demonstrated limited efficacy against solid tumors, primarily due to challenges posed by the solid tumor microenvironment. In contrast, radiotherapy, a well-established treatment modality, has been proven to modulate the tumor microenvironment and facilitate immune cell infiltration. With these observations, we hypothesize that a novel therapeutic strategy integrating CAR-NK cell therapy with radiotherapy could enhance the ability to treat solid tumors. This hypothesis aims to address the obstacles CAR-NK cell therapies face within the solid tumor microenvironment and explore the potential efficacy of their combination with radiotherapy. By capitalizing on the synergistic advantages of CAR-NK cell therapy and radiotherapy, we posit that this could lead to improved prognoses for patients with solid tumors.